C-Terminal Redox Domain of Arabidopsis APR1 Is a Non-Canonical Thioredoxin Domain with Glutaredoxin Function - Fang-Fang Chen; Chia-Yu Chien; Chao-Cheng Cho; Yu-Yung Chang; Chun-Hua Hsu (MDPI AG, 2019)
Sulfur is an essential nutrient that can be converted into utilizable metabolic forms to produce sulfur-containing metabolites in plant. Adenosine 5′-phosphosulfate (APS) reductase (APR) plays a vital role in catalyzing the reduction of activated sulfate to sulfite, which requires glutathione. Previous studies have shown that the C-terminal domain of APR acts as a glutathione-dependent reductase. The crystal structure of the C-terminal redox domain of Arabidopsis APR1 (AtAPR1) shows a conserved α/β thioredoxin fold, but not a glutaredoxin fold. Further biochemical studies of the redox domain from AtAPR1 provided evidence to support the structural observation. Collectively, our results provide structural and biochemical information to explain how the thioredoxin fold exerts the glutaredoxin function in APR.